2018
DOI: 10.1021/acs.molpharmaceut.8b00507
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Liquid Crystalline Systems for Controlled Drug Release and Improved Treatment of Vulvovaginal Candidiasis

Abstract: Vulvovaginal candidiasis (VVC) is the most common infection caused by Candida albicans and greatly reduces the quality of life of women affected by it. Due to the ineffectiveness of conventional treatments, there is growing interest in research involving compounds of natural origin. One such compound is curcumin (CUR), which has been proven to be effective against this microorganism. However, some of CUR's physicochemical properties, especially its low aqueous solubility, make the therapeutic application of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 75 publications
1
35
0
2
Order By: Relevance
“…The advantage of the microemulsion used here compared to the alginate-based nanoparticle is the in situ (i.e., in the vaginal mucosa) formation of a liquid crystalline system with a gellike appearance upon contact with water (Geraghty et al, 1996;Lopes et al, 2006;Phelps et al, 2011). The gel formed after ME swelling is more viscous, which improves the residence time in the vaginal canal (Geraghty et al, 1997;Rodero et al, 2018;Jie et al, 2019). Advantages resulting from this property include the lower probability of leaking after delivery and the possibility of reducing the dosing frequency compared to less viscous systems (Rodero et al, 2018;Jie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the microemulsion used here compared to the alginate-based nanoparticle is the in situ (i.e., in the vaginal mucosa) formation of a liquid crystalline system with a gellike appearance upon contact with water (Geraghty et al, 1996;Lopes et al, 2006;Phelps et al, 2011). The gel formed after ME swelling is more viscous, which improves the residence time in the vaginal canal (Geraghty et al, 1997;Rodero et al, 2018;Jie et al, 2019). Advantages resulting from this property include the lower probability of leaking after delivery and the possibility of reducing the dosing frequency compared to less viscous systems (Rodero et al, 2018;Jie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The gel formed after ME swelling is more viscous, which improves the residence time in the vaginal canal (Geraghty et al, 1997;Rodero et al, 2018;Jie et al, 2019). Advantages resulting from this property include the lower probability of leaking after delivery and the possibility of reducing the dosing frequency compared to less viscous systems (Rodero et al, 2018;Jie et al, 2019). Thus, the fluid ME can be considered a ready-to-use delivery system and does not need to be incorporated in a gel or in any other dosage form for administration since it spontaneously forms a gel in situ.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches include probiotics (e.g., Lactobacillus spp. ), or synthetic or natural-based compounds (e.g., polyphenols) that have been shown to have anti-inflammatory effects [184][185][186][187][188][189]. On the other hand, strategies to restore PMN antifungal activity during vaginitis by targeting HS would conceivably reduce the organism burden with a functional PMN response and ultimately restore the asymptomatic state.…”
Section: Strategies To Reduce Damagementioning
confidence: 99%
“…Recently, various targeted drug delivery systems have received attention for their ability of delivering drugs to cancer tissues in a highly selective manner without affecting other tissues. Such systems include nanoparticles [8], nanostructured lipid particles [9], liquid crystals (LC) [10], pH-responsive micelles [11], etc. LC have the ability to form an organized mesophase exhibiting both crystalline solid and liquid properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition rate of curcumin was found to be 74.33% [4,5]. Rodero et al reported that curcumin-loaded liquid crystalline systems with additional mucoadhesive properties are an efficient means of treating vulvovaginal candidiasis (VVC) upon vaginal administration [10]. Likewise, an in vitro study by Salmazi et al (2015) showed better potency of a curcumin-loaded LC precursor mucoadhesive system consisting of chitosan and poloxamer 407 compared with a curcumin solution against VVC [19].…”
Section: Introductionmentioning
confidence: 99%